Comparing four service delivery models for adolescent girls and young women through the 'Girl Power' study: protocol for a multisite quasi-experimental cohort study. Issue 12 (14th December 2017) - Rosenberg, Nora E; Pettifor, Audrey E; Myers, Laura; Phanga, Twambilile; Marcus, Rebecca; Bhushan, Nivedita Latha; Madlingozi, Nomtha; Vansia, Dhrutika; Masters, Avril; Maseko, Bertha; Mtwisha, Lulu; Kachigamba, Annie; et al.
Abstract : Introduction: In sub-Saharan Africa, adolescent girls and young women (AGYW) face a range of sexual and reproductive health (SRH) challenges. Clinical, behavioural and structural interventions have each reduced these risks and improved health outcomes. However, combinations of these interventions have not been compared with each other or with no intervention at all. The 'Girl Power' study is designed to systematically make these comparisons. Methods and analysis: Four comparable health facilities in Malawi and South Africa (n=8) were selected and assigned to one of the following models of care: (1) Standard of care : AGYW can receive family planning, HIV testing and counselling (HTC), and sexually transmitted infection (STI) syndromic management in three separate locations with three separate queues with the general population. No youth-friendly spaces, clinical modifications or trainings are offered, (2) Youth-Friendly Health Services (YFHS) : AGYW are meant to receive integrated family planning, HTC and STI services in dedicated youth spaces with youth-friendly modifications and providers trained in YFHS, (3) YFHS+behavioural intervention (BI) : In addition to YFHS, AGYW can attend 12 monthly theory-driven, facilitator-led, interactive sessions on health, finance and relationships, (4) YFHS+BI+conditional cash transfer (CCT) : in addition to YFHS and BI, AGYW receive up to 12 CCTs conditional on monthly BI session attendance. At each clinic, 250 AGYW 15–24 years old (n=2000 total) will be consented, enrolled and followed for 1 year. Each participant will complete a behavioural survey at enrolment, 6 months and 12 months . All clinical, behavioural and CCT services will be captured. Outcomes of interest include uptake of each package element and reduction in HIV risk behaviours. A qualitative substudy will be conducted. Ethics/dissemination: This study has received ethical approval from the University of North Carolina Institutional Review Board, the University of Cape Town Human Research Ethics Committee and Malawi's National Health Sciences Research Committee. Study plans, processes and findings will be disseminated to stakeholders, in peer-reviewed journals and at conferences.